2022
DOI: 10.3390/ijerph191710550
|View full text |Cite
|
Sign up to set email alerts
|

How Did People with Functional Disability Experience the First COVID-19 Lockdown? A Thematic Analysis of YouTube Comments

Abstract: People with functional disability endure barriers to health and other services and to full participation in social life. In the context of COVID-19, this discrimination has been intensified worldwide. We examine how the experience of COVID-19 lockdown was depicted in comments to a video about functional disability and COVID published on VICE’s YouTube channel. We analysed the first 100 comments on the video, which was posted in spring 2020, during the first COVID-19 lockdown (roughly from March to June 2020, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…For example, some people with disabilities turned to social media for support during the COVID-19 pandemic to partially offset the doubly isolating effects of disability and pandemic precautions. 63 On average, participants with greater active social media use did report greater social support than those with less active use, which may include social support received on social media. Consistent with the literature showing a robust relationship between social support and health, 64,65 those with greater social support had better health indicators.…”
Section: Discussionmentioning
confidence: 92%
“…For example, some people with disabilities turned to social media for support during the COVID-19 pandemic to partially offset the doubly isolating effects of disability and pandemic precautions. 63 On average, participants with greater active social media use did report greater social support than those with less active use, which may include social support received on social media. Consistent with the literature showing a robust relationship between social support and health, 64,65 those with greater social support had better health indicators.…”
Section: Discussionmentioning
confidence: 92%
“…Inevitably, internet use has negative effects. Considering the potential barriers to smartphone use ( 56 ) or the difficulty of indulging in the media environment due to the simple purpose of use and the short time of use ( 22 ), the impact of the internet on the mental health of middle-aged and older adults is moderate and positive.…”
Section: Discussionmentioning
confidence: 99%
“…Network informatization has contributed significantly to improving the life satisfaction of people with mobility disabilities ( 20 ), and may help increase internet use and use of virtual media as a means of meeting people ( 21 ). Related research has shown that analysis of online media can be an effective way to understand the health experiences of people with functional disability ( 22 ). Therefore, under the multiple backgrounds of digitalization and aging, it is still necessary to pay attention to how the middle-aged and older groups benefit from the internet.…”
Section: Introductionmentioning
confidence: 99%
“…The setbacks in the human rights of people with disabilities have also been denounced (European Disability Forum, 2020;Solomon et al, 2020). New forms of discrimination that have emerged during the pandemic, clearly showing the urgency for the improvement of health crisis management in the future (Hall et al, 2022). This autoethnography contributes to this corpus offering insight into the specific experience of COVID-19 lockdown of a person born with a physical disability.…”
Section: Introductionmentioning
confidence: 90%
“…In line with the emancipatory disability approach (Barnes, 2004;Berger, 2016;Oliver, 1997), I resist reading disability as tragic or pitiable, focusing instead on self-care, agency, and resilience building. In fact, people born with a physical disability, being the only social group for whom restricted mobility is their normal, showed themselves to be prepared for isolation and mobility limitations imposed with the COVID-19 outbreak (Chou et al, 2021;Hall et al, 2022).…”
Section: Introductionmentioning
confidence: 99%